2020
DOI: 10.1016/j.epsl.2020.116202
|View full text |Cite
|
Sign up to set email alerts
|

Crack to pulse transition and magnitude statistics during earthquake cycles on a self-similar rough fault

Abstract: Faults in nature demonstrate fluctuations from planarity at most length scales that are relevant for earthquake dynamics. These fluctuations may influence all stages of the seismic cycle; earthquake nucleation, propagation, arrest, and inter-seismic behavior. Here I show quasi-dynamic plane-strain simulations of earthquake cycles on a self-similar and finite 10 km long rough fault with amplitude-to-wavelength ratio α = 0.01. The minimum roughness wavelength, λ min , and nucleation length scales are well resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…A similar transition from few large ruptures to many smaller ones was found by Heimisson (2020) when increasing k max ; since the amplitude of normal stress perturbations grows with k max (Equation 10), this is consistent with our findings. Similarly, we expect that increasing fault roughness would have the same effect, since Δ σ rms increases with the product of roughness and accrued slip.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A similar transition from few large ruptures to many smaller ones was found by Heimisson (2020) when increasing k max ; since the amplitude of normal stress perturbations grows with k max (Equation 10), this is consistent with our findings. Similarly, we expect that increasing fault roughness would have the same effect, since Δ σ rms increases with the product of roughness and accrued slip.…”
Section: Discussionsupporting
confidence: 93%
“…Perhaps the most ubiquitous and best characterized source of heterogeneity is geometrical roughness: faults are fractal surfaces (Brodsky et al., 2016; Candela et al., 2009, 2012; Power & Tullis, 1991; Power et al., 1987, 1988; Sagy et al., 2007). Numerical and theoretical studies have shown that fault roughness has a first‐order effect on rupture nucleation (Tal et al., 2018), as well as propagation and arrest (Dunham et al., 2011; Fang & Dunham, 2013; Heimisson, 2020; Ozawa et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Slip on a rough fault produces an additional shear resistance, which is expressed as τdrag=false(2πfalse)3α2Gδ/λmin, where δ is slip and H is the Hurst exponent. Roughness drag enhances pulse‐like ruptures and deviation from the classical elliptic crack (Dieterich & Smith, 2009; Heimisson, 2020), which reduces the stress concentration at the fault tips.…”
Section: Resultsmentioning
confidence: 99%
“…The pulse‐like ruptures only occur and the effect of roughness drag is only important if the rupture length is larger than λ min /(4 π 4 α 2 ) (Heimisson, 2020). Otherwise, the classical elliptic crack is realized and the stress concentration around the tips is strong.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Tarduno et al (2015) argued that SAMA is being created by a topography structure in the CMB beneath southern Africa. Not only is SAMA linked with global magnetic features such as a geomagnetic dipole moment (e.g., Heirtzler, 2002;Gubbins et al, 2006), it also corresponds to the closer area between the Earth's surface and radiation belt. This proximity allows more charged particles and more disturbances in the magnetic field near the Chilean margin (e.g., Kivelson and Russell, 1995).…”
Section: Secular Variation In the Chilean Convergent Marginmentioning
confidence: 99%